The Effect of Financial Scandals on Regulation and its Impact on Corporate Financial Decisions - Nurdin, Maryam (Advances in Applied Accounting Research, 2025)
Purpose: This study analyzes the effects of financial scandals on regulatory reforms and their impact on corporate financial decision-making. The research explores how regulatory changes influence financial strategies, focusing on differences in corporate adaptation in developed and developing markets. Research Design and Methodology: The study employs a qualitative systematic literature review (SLR) approach, synthesizing findings from peer-reviewed journals, books, and reports. The analysis integrates theoretical perspectives, such as agency theory, to comprehensively understand the dynamics between financial scandals, regulatory changes, and corporate financial strategies. Findings and Discussion: The findings indicate that financial scandals significantly drive regulatory reforms to strengthen transparency and accountability. Companies respond to these reforms by adjusting their capital structure, debt management, and investment strategies. Advanced technologies like blockchain and artificial intelligence (AI) have become pivotal in enhancing compliance and reporting efficiency. However, technological adoption presents challenges, particularly for companies in developing markets that face financial and infrastructure constraints. The study highlights that the success of regulatory reforms depends on robust enforcement mechanisms, stakeholder collaboration, and institutional support. Differences in corporate adaptation underscore the importance of tailored regulatory approaches to balance financial oversight and corporate flexibility. Implications: The study offers practical insights for policymakers and corporate leaders in formulating regulatory frameworks that foster innovation while maintaining financial integrity. Recommendations include simplifying compliance processes, providing technical guidance, and offering incentives for digitalization. These strategies can enhance corporate resilience and contribute to sustainable economic growth.